Análise cladística e descrição de um grupo novo de espécies de Edessa (Heteroptera, Pentatomidae, Edessinae) - SILVA, Valéria Juliete da (Universidade Federal do Pará, 2013)
The suborder Heteroptera, is one of the largest hemimetabolic taxa and currently composed by seven infraorders, 23 superfamilies and 80 families. Pentatomidae is the fourth most numerous and diverse family among heteropterans having 4100 species in 760 genera and seven subfamilies. Edessinae has almost 290 species distributed in six genera: Edessa, Brachystethus, Peromatus, Olbia, Pantochlora and Doesburgedessa. Among these genera Edessa concentrates almost all species as well as most of the taxonomical and nomenclatural problems of the subfamily. Due to its size, the revision is being made in parts, from the study of groups of species united by characteristics that are possible synapomorphies.Thus, the aim of this work is to propose and describe a new group of species based on a cladistic analysis. For the study were examined 114 specimens belonging to national and international collections. Descriptions were made following a traditional method also used for Edessinae. Photos and measurements of the species, line art drawings from metasternal process and genitalia of both sexes, key and distribution map are also provided. For the cladistic analysis 22 morphological characters were raised and polarized using an out group composed of Tibilis sp., Neotibilis fulvicornis, Brachystethus cribrus, Pantochlora vivida, Olbia elegans, Peromatus sp., Doesburgedessa elongatispina, Edessa cervus and Edessa affinis. Analysis was performed using NONA and a single tree with 30 steps, Consistency Index=0,93 and Retention Index=0,97 was obtained. Based on this analysis, the monophyly of the target group of species was confirmed. Thus, the group stolida is here proposed to include four species already described (Edessa stolida (Linnaeus, 1758), Edessa heymonsi Breddin, 1904, Edessa verhoeffi Breddin, 1904 and Edessa paravinula Barber, 1935) and five new species. The group stolida of Edessa is recognized by a protruding process of the posterior side of segment X; medial region of paramere with a triangular projection; absence of a distal band or tuft of hair on segment X; and gonapophyse 8 sclerotized. Species of the group stolida were differentiated only by the external genitalia of both sexes. The cladistic analysis supports the traditional view and the stolida group should be considered part of the subgenus Hypoxys of Edessa. Topology of the cladograma resultant is (Tibilis sp + Neotibilis fulvicornis (Brachystethus cribrus (Pantochlora vivida ((Doesburgedessa elongatispina + Edessa cervus (Peromatus sp. + Olbia elegans)) (Edessa affinis ((Edessa sp. nov 3 + Edessa sp. nov 3a) ((Edessa sp. nov 2 (Edessa verhoeffi+ Edessa heymonsi)) (Edessa stolida (Edessa sp. nov 4 (Edessa paravinula + Edessa sp. nov 5 ))))))))). The female of Edessa stolida and male of Edessa verhoeffi were described here for the first time. The records of species distribution are expanded.